Mapping determinants of career choice among Omani university students: Institutional, social, and personal influences - Fernandez, Diana; Raveendran, Renjith Kumar; Al Shukaili, Nahid Abdullah Sulaiyam (Journal of International Students, 2026)
This study examines the factors influencing career choice certainty among university students in Oman. Guided by Bronfenbrenner’s Ecological Systems Theory, Human Capital Theory, and Social Capital Theory, eight domains are analyzed: academic background, on-the-job training, institutional support, finances, personality, social influences, sectoral opportunities, and public policy. Data from 380 students across seven campuses were analyzed using exploratory factor analysis and regression. Academic specialization, mentoring, risk-taking, and extracurricular involvement emerged as significant predictors, whereas financial and policy factors were less influential. The findings emphasize the critical role of institutional support systems in shaping career development, with implications for enhancing student readiness and support strategies in both domestic and international mobility contexts in higher education.